MENGENAL PENGOBATAN INFLUENZA DARI TINJAUAN MEDIS DAN SYARI’AH - Wijaya, Liza; Aini, Nur; Rahmawati, Ayu (ABDIMAS Madani, 2023)
Influenza is a disease that attacks the respiratory tract caused by various types of influenza viruses and can be transmitted through the air. Transmission can occur easily through droplets when an infected person coughs or sneezes. Treatment of influenza is symptomatic and supportive. Symptomatic treatment in the early stages may be self-administered and may require medication if symptoms persist. In addition to treatment under medical review, there is also treatment under Sharia review. There are several actions that Thibbun Nabawi can take. This understanding needs to be given to the elderly to increase their understanding of Islamic medicine and how to properly manage herbal ingredients. This community service was held in January 2023 and was attended by 69 elderly people in Sinduharjo Village, Sleman Regency who are members of the Dakwah Garage community. Activities carried out are counseling, free health checks, and exercise for the elderly. The results of the evaluation showed an increase in knowledge after being given counseling. Low knowledge 10 people (14.5%), moderate knowledge 30 people (43.5%), high knowledge 29 people (42.0%)